Raça em formação de galinhas de plumagem azul e ovos azuis - Graner, E. A.; Torres, A. P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1949)
This paper deals with the inheritance of black, blue and blue-splashed plumage in poultry. The material analysed had its origin in the State of Goias, Brazil and the genetical data seems to indicate the interaction of a single pair of genes as in the Andalusian fowls and other blue breeds. The dominant gene for blue egg is also present in the material and selection is now being directed to isolate a breed with blue plumage and blue eggs, named "Tudo Azul", what in Portuguese means all blue (plumage and eggs) and corresponds, in braziliian slang, to the expression "O. K." used in the United States. The commercial possibility of the chickens, as judging by its, laying capacity, is emphasized.